2011
DOI: 10.1055/s-0030-1267104
|View full text |Cite
|
Sign up to set email alerts
|

Dropped head syndrome: diagnosis and management

Abstract: Dropped head syndrome (DHS) is a relatively rare condition, with a broad differential diagnosis. This deformity has significant implications on the health and quality of life of affected individuals. While surgery seems to be an obvious therapeutic option, there is a paucity of information on surgical intervention with no clear consensus on an optimal approach or timing.We present a case of DHS in a young woman to illustrate this condition, and review the current literature. Although at present the only defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 31 publications
0
59
0
Order By: Relevance
“…A complete inability to normalize neck flexion may be seen with the progression of dropped head syndrome. This may result in muscle contracture, secondary spinal degenerative changes, and cervical myelopathy . Patients report that pain may accompany dropped head syndrome as a result of involuntary muscle spasm or secondary or associated degenerative joint disease of the cervical spine .…”
Section: Postural Disorders (Spine)mentioning
confidence: 99%
See 1 more Smart Citation
“…A complete inability to normalize neck flexion may be seen with the progression of dropped head syndrome. This may result in muscle contracture, secondary spinal degenerative changes, and cervical myelopathy . Patients report that pain may accompany dropped head syndrome as a result of involuntary muscle spasm or secondary or associated degenerative joint disease of the cervical spine .…”
Section: Postural Disorders (Spine)mentioning
confidence: 99%
“…This may result in muscle contracture, secondary spinal degenerative changes, and cervical myelopathy. 35 Patients report that pain may accompany dropped head syndrome as a result of involuntary muscle spasm or secondary or associated degenerative joint disease of the cervical spine. 3 It has been reported that the positioning sometimes restores itself to the upright or extended position in the later stages of PD, perhaps because tonus of the neck extensor muscles may come to exceed that of the flexor muscles.…”
Section: Dropped Head Syndromementioning
confidence: 99%
“…However, the invasiveness of a posterior instrumented fusion is probably unacceptable compared with the incidence of postoperative DHS. Furthermore, posterior instrumented fusion of the cervical spine cannot necessarily prevent postoperative DHS because it often involves cervicothoracic kyphosis, not just cervical kyphosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical collars are widely prescribed as first‐line treatment for mechanical stabilization in this condition . Potential orthotic options for mechanical stabilization of DHS include the use of soft or hard collars, sternal occipital manual immobilizer (or SOMI) brace, and halo‐vest . Alternative braces, such as the baseball cap orthosis, have been described previously, but there are limited objective studies that measure patient compliance and describe the utility of such braces in activities of daily living.…”
Section: Introductionmentioning
confidence: 99%